Programmed Cell Death in Cancer Progression and Therapy - Khosravi-Far, Roya.; White, Eileen; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2008)
Programmed cell death (PCD) plays pivotal roles in tumor progression, cancer therapeutics and resistance of tumor cells to therapy. With the discovery of key mechanisms that are involved in mediating PCD and in promoting resistance to therapy, design of therapeutic approaches for promoting tumor-selective cell death has risen dramatically. With this book, we give a comprehensive overview of the mechanisms that are involved in mediating and regulating PCD in cancer. We also provide a detailed indication of the utility of PCD in cancer therapy. This book will be a valuable resource for researchers investigating the role of PCD in cancer and other diseases, researchers investigating the molecular mechanism of chemotherapeutic agents and drug-resistance in cancer and for physicians using chemotherapeutic agents. Additionally, this book will be a important educational source for PhD students specializing in cell biology, immunology and MD students interested in Oncology and Cancer Therapeutics.
Cell Death: History and Future -- Caspase Mechanisms -- The Mitochondrial Death Pathway -- Apoptotic Pathways in Tumor Progression and Therapy -- Therapeutic Targeting of Death Pathways in Cancer: Mechanisms for Activating Cell Death in Cancer Cells -- Overcoming Resistance to Apoptosis in Cancer Therapy -- Trail Receptors: Targets for Cancer Therapy -- Rational Design of Therapeutics Targeting the BCL-2 Family: Are Some Cancer Cells Primed for Death but Waiting for a Final Push? -- Autophagy and Tumor Suppression: Recent Advances in Understanding the Link between Autophagic Cell Death Pathways and Tumor Development -- Regulation of Programmed Cell Death by the P53 Pathway -- Regulation of Programmed Cell Death by NF-?B and its Role in Tumorigenesis and Therapy -- Targeting Proteasomes as Therapy in Multiple Myeloma -- Histone Deacetylase Inhibitors: Mechanisms and Clinical Significance in Cancer: HDAC Inhibitor-Induced Apoptosis -- RNA Interference and Cancer: Endogenous Pathways and Therapeutic Approaches -- Cancer Stem Cells and Impaired Apoptosis.
Keywords: Medicine; Cancer research; Immunology; Molecular biology; Oncology; Cell biology; Biomedicine; Cancer Research; Cell Biology; Molecular Medicine; Immunology; Oncology; Electronic books